Types of plants that are used for postpartum care and conservation efforts in Singkil Subdistrict - HASANUDDIN HASANUDDIN; ASIAH ASIAH; VIVERA RUSELLI PUSPA; WARDIAH WARDIAH; DEWI ANDAYANI (Jurnal Natural, 2022)
Inventory of postpartum care plants is a collection of types of plants used by the community in healing postpartum care. This study aims to find out the types, parts, and ways of processing plants used in postpartum care as well as conservation efforts made to plants that have the potential as postpartum care in Singkil District, Aceh Singkil Regency. The research was conducted in July until August 2020, and data collected using a qualitative descriptive method with structural observations and interviews. The data source taken was 50 respondents consisting of 10 physicians, 10 midwives, and 30 mothers who had given birth. Data analysis is done descriptively using a qualitative approach. The results of the study obtained 31 species of plants used for postpartum care, parts of plants used to consist of fruit, seeds, stems, flowers, leaves, tubers, and rhizomes, the processing was carried out by boiling and grinding.